Respuesta :

Answer:

  (n -4)(n +1)^2 = n^3 -2n^2 -7n -4

Step-by-step explanation:

The least common denominator is the smallest denominator that lets you write the sum as a single fraction.

  [tex]\dfrac{n^5}{n^2+2n+1}+\dfrac{-4}{n^2-3n-4}=\dfrac{n^5}{(n+1)^2}+\dfrac{-4}{(n+1)(n-4)}\\\\=\dfrac{n^5}{(n+1)^2}\cdot\dfrac{n-4}{n-4}+\dfrac{-4}{(n+1)(n-4)}\cdot\dfrac{n+1}{n+1}=\dfrac{n^5(n-4)-4(n+1)}{(n+1)^2(n-4)}\\\\=\dfrac{n^6-4n^5-4n-4}{n^3-2n^2-7n-4}[/tex]

The least common denominator is ...

  (n-4)(n+1)^2 = n^3 -2n^2 -7n -4